Job insecurity, employee incivility and coaching perception of casino employees: A moderated mediation model* - Saydam, Mehmet Bahri; Arasli, Huseyin; Arici, Hasan Evrim (Nomos Verlagsgesellschaft Mbh & Co Kg, 2023)
This paper aims to analyze job insecurity (JIS)'s effect on employee incivility by mediating the role of moral disengagement (MD) and the moderating role of coaching behavior in the casino sector. Data was collected from 542 casino employees in Northern Cyprus. The study showed that casino employees' MD mediated the association between JIS and employee incivility. Additionally, coaching behavior moderated the path of this mediated link. Due to the limited endeavors on the hypothesized relationships, the research contributes to the literature and industry.
Keywords: Moral disengagement; incivility; job insecurity; coaching behavior; hospitality